Epigenome-wide DNA methylation study of IgE concentration in relation to self-reported allergies. (April 2017) - Ek, Weronica E; Ahsan, Muhammad; Rask-Andersen, Mathias; Liang, Liming; Moffatt, Miriam F; Gyllensten, Ulf; Johansson, Åsa
Aim: Epigenetic mechanisms are critical for normal immune development and epigenetic alterations might therefore be possible contributors to immune diseases. To investigate if DNA methylation in whole blood is associated with total and allergen-specific IgE levels.Methods: We performed an epigenome-wide association study to investigate the association between DNA methylation and IgE level, allergen-specific IgE and self-reported immune diseases and allergies in 728 individuals.Results: We identified and replicated 15 CpG sites associated with IgE, mapping to biologically relevant genes, including ACOT7, ILR5A, KCNH2, PRG2 and EPX . A total of 331 loci were associated with allergen-specific IgE, but none of these CpG sites were associated with self-reported allergies and immune diseases.Conclusion: This study shows that IgE levels are associated with DNA methylation levels at numerous CpG sites, which might provide new leads for investigating the links between IgE and allergic inflammation.